Proportion of circulating tumor cell clusters increases during cancer metastasis. Issue 3 (23rd December 2016) - Suo, Yuanzhen; Xie, Chengying; Zhu, Xi; Fan, Zhichao; Yang, Zhangru; He, Hao; Wei, Xunbin
Abstract: Circulating tumor cell (CTC) clusters are found among CTCs and show significantly greater potential for an important role in cancer metastasis than single CTCs, which have been traditionally believed as the majority of CTCs. The accurate proportion and dynamics of CTC clusters remain unclear due to the fact that CTCs in blood flow are very difficult to detect in vivo and in vitro. CTC clusters are even more difficult to be distinguished from CTCs without perturbation by state‐of‐the‐art detection methods. Here, we demonstrate that by using in vivo flow cytometry (IVFC), we can reliably measure the proportion and dynamics of CTC clusters in two murine tumor models. CTC clusters are easily identified by their unique fluorescent pattern with multiple peaks and wider time duration. We find that the proportion of CTC clusters increases significantly during cancer metastasis in both mouse models, the orthotopic liver cancer and the subcutaneous prostate cancer models. Our results suggest that CTC clusters account for a much larger proportion of CTCs than previously anticipated. Hence this report might provide a new‐level of understanding of CTCs during cancer development and progression. © 2016 International Society for Advancement of Cytometry